1970
DOI: 10.3126/njms.v1i1.5796
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dependence Syndrome Among Older Adults Attending Psychiatry OPD of a Private Hospital in Western Region of Nepal

Abstract: Background: Alcohol use disorders in elderly people are common and associated with considerable morbidity. The objective is to estimate the prevalence of alcohol dependence syndrome among elderly patients attending psychiatric outpatient department of a private hospital in Western region of Nepal. Methods: A total of 80 elderly patients aged 65 years and above who attended the psychiatry outpatient department of Fewa City Hospital and Research Centre, Pokhara, Nepal were included in the study. A semistructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…11 In a study done in Western Region of Nepal, 5% of total subjects had alcohol dependence syndrome. 17 This prevalence is slightly less than that of our study. Our study showed higher prevalence of alcohol dependence than similar studies done in other part of Nepal.…”
Section: Psychiatric Morbiditiescontrasting
confidence: 54%
“…11 In a study done in Western Region of Nepal, 5% of total subjects had alcohol dependence syndrome. 17 This prevalence is slightly less than that of our study. Our study showed higher prevalence of alcohol dependence than similar studies done in other part of Nepal.…”
Section: Psychiatric Morbiditiescontrasting
confidence: 54%
“…This patient was diagnosed to be suffering from alcohol dependence syndrome. Other studies done previously in Nepal found prevalence of 5%, 25 10.5%, 14 12.9%, 15 14%, 23 18.1% 13 and 19%. 16 …”
Section: Discussionmentioning
confidence: 61%
“…One study conducted in the same Province area as the current study also found more elderly males to be suffering from alcohol dependence syndrome. 25 One study done in Nepal found more prevalence of alcohol dependence and dementia in the male population. 13 There is more prevalence of all psychiatric diagnoses in the patients less than or equal to 75 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from Nepal have reported alcohol dependence syndrome in 5% of elderly patients,[ 8 ] and alcohol related disorders in 14%. [ 4 ] Similar high prevalence of alcohol related problems (11.7%) was found in our study.…”
Section: Discussionmentioning
confidence: 99%